Evaluation of bioactive peptides from kenaf (Hibiscus cannabinus L.) seed protein for angiotensin-converting enzyme inhibitory activity - Zaharuddin, Nurul Dhania (2022)
The aim of this study was to produce bioactive peptides synthesized from kenaf (Hibiscus cannabinus L.) seed, which is a byproduct of the kenaf industry and investigate on its antihypertensive activity. Kenaf seed was observed to produce 12.2 % yield, with 70.2 % protein content. Papain-generated hydrolysates was observed to produce a very high angiotensin-converting enzyme (ACE) inhibitory activity, with 95.47 %. Therefore, it was decided that papain-generated hydrolysates to be further studied. Optimum condition of 65 °C, pH 6.5, 2.25 hours and E/S ratio 0.03 was determined and produced a maximum degree of hydrolysis (DH) of 58.98 % and 78.45 % ACE inhibitory activity. It was observed that the solubility, foaming and emulsification activity was low at pH 4 and increased up to pH 9 and the water and oil absorption capacity was observed to be lower in kenaf seed protein hydrolysate (KSPH) as compared to kenaf seed protein isolate (KSPI). The in vivo biological activity of KSPH was observed to be the most optimum dosage at 300 mg/kg. Profiling of the peptides showed that peptides with molecular weight 2 to 5 kDa exerted the highest ACE inhibitory (82.27 %) with hydrophobic peptides in the later-eluting fractions. Sequencing showed that peptides INPPSTTN, AKSCVVFP, LLLHAL, WTIPTPS, ALFYWVS and LYWSYLYN possessed high ACE inhibitory activities. Molecular docking reflected that peptide LYWSYLYN with the lowest Glidescore value (-14.66 kJ/mol) possessed the strongest binding affinity towards the ACE protein and kinetic studies discovered that peptide LYWSYLYN which underwent competitive inhibition displayed the lowest Ki value (0.017 mM) which was indicated the most effective ACE inhibitor amongst the other peptides. Thus, it can be concluded that bioactive peptides derived from kenaf seed protein has high ACE inhibitory activity which is a potential functional food ingredient for development of various food applications.